Efektifitas Pengelolaan Manajemen Pergudangan Terhadap Sistem Distribusi Beras pada Pemerintah Daerah DKI Jakarta - Heryadi, Muhammad Heri; Nofrisel, Nofrisel; Sugiharti, Endang; Simarmata, Juliater; Anggara, Dian Christopher (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2024)
DKI Jakarta experienced the rice production deficit of 99.61% in 2020. The problem arised because DKI Jakarta could fulfill its rice necessity from other cities and the poor management of the warehouse and distribution system. The aim of the study is to propose a warehouse management to improve the effective distribution system. The study used qualitative descriptive research method. There were 16 officials of the warehouse management and distribution system in PT. Tjipinang Jaya Food Station as the participants. The data was processed using the credibility, transferability, dependability and confirmability tests approaches. The results of the study indicate that the warehouse management and distribution system in PT. Tjipinang Jaya Food Station is considered ineffective and inefficient in improving food security operation in DKI Jakarta. The evidence found is the absorption or the less than demand purchase of the product, which is 2,665 tons with a total demand of 688,226 tons. The problem with inequality distribution, decreased quantity in the distribution process, raw materials received delay, unfulfilled delivery of finished material to consumers and uncertainty of the warehouse utilization planning are factors needed to be restored continuously in the future.